Art Therapy untuk Mengatasi Hambatan Komunikasi Emosional pada Individu dengan Gangguan Kecemasan: Studi dengan Metode Ekspresi Visual - Wahyu Dwi Cahyani; Hidayatul Fikra (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2025)
Individuals with anxiety disorders often experience emotional communication barriers that limit the effectiveness of conventional verbal therapy. This study aims to explore the effectiveness of visual expression-based art therapy in overcoming emotional communication barriers in anxiety disorders. This study uses a qualitative approach with a narrative literature review method by synthesizing theoretical and empirical literature related to emotional communication barriers in individuals with anxiety disorders. This study found that visual expression-based art therapy can help overcome emotional communication barriers in individuals with anxiety disorders. Through visual media, individuals can express emotions that are difficult to articulate verbally, thereby facilitating more adaptive emotional processing. These findings indicate that art therapy works through a bottom-up mechanism by accessing nonverbal memories and implicit emotions, which are then integrated into cognitive understanding. Neuropsychologically, the creative process in art therapy is associated with decreased amygdala activity, increased prefrontal cortex function, and improved emotional regulation, which contribute to a reduction in anxiety symptoms. Thus, art therapy does not replace verbal therapy, but rather serves as a complementary approach that provides an alternative pathway for emotional communication for individuals with verbal limitations.